Laminin 511-E8 Fragment Offers Superior Adhesion Properties for Gastric Cancer Cells Compared with Full-Length Laminin 511 - Masaya Iwamuro; Hidenori Shiraha; Mayu Kobashi; Shigeru Horiguchi; Hiroyuki Okada (Current Issues in Molecular Biology, 2022)
Background: The interaction between cancer cells and laminin (Ln) is a key event in tumor invasion and metastasis. Previously, we determined the effect of full-length Ln511 on gastric cancer cells. However, the interactions between the Ln511-E8 fragment, a truncated protein of Ln511, and gastric cancer cells have not been investigated. Methods: We investigated the adhesion properties of gastric cancer cells to full-length Ln511 and Ln511-E8 fragments. Results: The proliferation of four gastric cancer cell lines (SH-10-TC, MKN74, SC-6-JCK, and MKN45) was highest on the Ln511-E8 fragment. Further, a larger cytoplasm was observed in SH-10-TC and MKN74 cells cultured on full-length Ln511 or Ln511-E8 fragments. The percentage of adhesive cells was highest on the Ln511-E8 fragment in all four cell lines. Moreover, adhesion of the gastric cancer cells to Ln511-E8 fragment-coated plates was reduced by the Cdc42 GTPase inhibitor in a dose-dependent manner, suggesting the involvement of Cdc42 in the Ln511-E8 fragment-induced enhanced adhesion of gastric cancer cells. Conclusions: The Ln511-E8 fragment had a greater impact on the adhesion, morphology, and proliferation of gastric cancer cells than full-length laminin. Thus, the Ln511-E8 fragment is suitable for investigating the interaction between gastric cancer cells and extracellular matrices in tumor invasion and metastasis.